PROHIBITION OF POLYGAMY WOMEN CIVIL SERVANTS IN A GENDER PERSPECTIVE : Criticism Against PP No. 10 of 1983 Jo PP No. 45 of 1990 - Yusmita (NUSANTARA: Journal Of Law Studies, 2023)
This paper discusses the juridical analysis regarding the prohibition of polygamous female civil servants (PNS). In Indonesia, regulations regarding this prohibition are contained in PP No. 10 of 1983 Jo PP No. 45 of 1990 article 4 paragraph. This research has a normative juridical focus. This type of research is expository analytical, describing and evaluating research topics. The study results indicate that the rules prohibiting female civil servants from becoming second, third, or fourth wives are legally recognized and must be applied and have legal force. However, from a review of Islamic law and higher positive law, namely marriage laws, This should be permissible because work has nothing to do with marriage, as it is permissible for a man to have polygamy with more than two wives under strict conditions. This makes it discriminatory for female civil servants because male civil servants may practice polygamy, while female civil servants may not be polygamous as second, third, and fourth wives. From a gender perspective, it can be concluded that the regulation regarding the prohibition of polygamy in female civil servants contains discrimination against women which does not reflect gender equality and justice, so this regulation needs to be reviewed. If male Civil Servants are allowed to have polygamy, then female Civil Servants should also be allowed to become second, third, or fourth wives. If female civil servants are not allowed to have second, third, and fourth wives, then male civil servants should also not be allowed to have polygamy.